Towards autonomous construction equipment - supporting on-site collaboration between automatons and humans. (24th February 2020) - Frank, Martin; Ruvald, Ryan; Johansson, Christian; Larsson, Tobias; Larsson, Andreas
To support the application of automated machines and collaborative robots in unstructured environments like in the mining, agriculture and construction sector the needs of the human co-worker should be investigated to ensure a safe and productive collaboration. The empirical study presented includes the prototyping of a solution for human-machine communication, which has been supported by a design thinking approach. An understanding of the human needs had been created through jobsite observations and semi-structured interviews with human workforces working in close proximity to heavy mobile equipment. The results show that trust and communication have a big impact on the jobsite collaboration.